Enrique Dussel's Ethics of Liberation An Introduction - Mills, Frederick B. (Springer International Publishing, 2018)
This book introduces the methodology and basic concepts of Dussel's ethics of liberation. Enrique Dussel is one of the principal founders of the philosophy of liberation in Latin America. Frederick B. Mills discusses how, for Dussel, we can realize our co-responsibility for human life by responding, in accord with ethical principles, to the appeals of victims of the prevailing capital system. Mills shows how these principles, when subsumed in the political and economic fields, aim at overcoming the ongoing assault on human life and nature and provide a moral compass for forging a path to liberation. He makes the case that the study of Dussel is critical to the understanding of liberatory thought in Latin America today. This book aims to introduce the ethics of liberation to a broader audience in the Global North where Dussel's ideas are urgently relevant to progressive political and economic theory and praxis.